Endometriosis - Molina Navia, Lucas (2015)
The positive developments of recent times in the field of endometriosis have been aimed toward verification of the primitive theory of Sampson and its rational application in the understanding and explanation of the disease. In a study of 5,930 patients hospitalized after surgery it has been checked 45 cases of endometriosis. Incidence: 0.75% - This figure does not represent the true incidence of endometriosis among us and belongs to a selected group of ill to attend common services Loayza hospital.